Does Dopamine Depletion Trigger a Spreader Lexical-Semantic Activation in Parkinson’s Disease? Evidence from a Study Based on Word Fluency Tasks - S. Zabberoni; G. A. Carlesimo; A. Peppe; C. Caltagirone; A. Costa (Parkinson's Disease)
It has been hypothesised that, in Parkinson’s disease (PD), dopamine might modulate spreading activation of lexical-semantic representations. We aimed to investigate this hypothesis in individuals with PD without dementia by assessing word frequency and typicality in verbal fluency tasks. We predicted that the average values of both of these parameters would be lower in PD patients with respect to healthy controls (HC). We administered letter-cued and category-cued fluency tasks to early PD patients in two experimental conditions: the tasks were administered both after 12–18 hours of dopaminergic stimulation withdrawal (“OFF” condition) and after the first daily dose of dopaminergic therapy (“ON” condition). HC were also given the two tasks in two conditions with the same intersession delay as PD patients but without taking drugs. Results showed that in both OFF and ON treatment conditions PD patients did not differ from HC in word frequency or typicality. Moreover, in the PD group, no significant difference was found between the experimental conditions. Our results show that semantic spreading was not altered in the PD sample examined; this suggests that in early PD the functioning of the semantic system is relatively independent from the activity of dopamine brain networks.